Current strategies in radiotherapy of head and neck cancer - Pütz, M. (German Medical Science GMS Publishing House, 2012)
The Intensity Modulated Radiation Therapy (IMRT) together with Image Guided Radiation Therapy (IGRT) improves radiation therapy for head and neck cancer. On the one hand tumors can be better covered with radiation dose and on the other hand normal tissue can be better preserved. Carefully applied this leads to the same tumor control rate with reduced toxicity compared with conventional radiation therapy. Respective to the addition of systemic therapy to irradiation therapy, platinum based radiochemotherapy remains the standard of care and there are first indications, that at least in the primary treatment of head and neck cancer the addition of Cetuximab to a cisplatin-based radiochemotherapy did not improve outcome.